Reactive iron, not fungal community, drives organic carbon oxidation potential in floodplain soils. (March 2023) - Naughton, Hannah R.; Tolar, Bradley B.; Dewey, Christian; Keiluweit, Marco; Nico, Peter S.; Fendorf, Scott
Abstract: Wetlands host ∼20% of terrestrial organic carbon and serve as a major sink for atmospheric carbon. Anoxic soils and sediments accrue soil organic carbon (SOC) partly by hampering the activity of extracellular oxidative enzymes that break down phenolic polymers. Upon aeration, fungal-driven oxidative enzymatic depolymerization and microbial respiration of released monomers ensue. Redox-active metals can simultaneously catalyze abiotic nonspecific oxidation of SOC, notable examples including Mn(III) or Fe(II) through Fenton-like, hydrogen peroxide-catalyzed oxidative radical production. However, the extent of reactive metal contributions to biotic and abiotic SOC degradation is not understood in the context of natural environments with diverse redox chemistry. We tested the relative contributions of fungi, Mn(III) and Fe(II) to phenolic substrate (L-DOPA) oxidation in floodplain soils representing a range of transient redox conditions driven by permanent vs. periodic flooding. Phenol oxidative potential was highest in permanently flooded soils with fewer fungal taxa known for observed (per)oxidase activity and instead correlated with HCl-extractable Fe(II), Fe(total) and Fe(II)/Fe(total), suggesting a specific role of Fe(II). Fe(II) additions enhanced phenol oxidative potential in sterilized and non-sterilized soils in the presence of hydrogen peroxide, indicating abiotic Fe-mediated radical chemistry could significantly enhance wetland SOC oxidative depolymerization throughout redox-active floodplain soils. Fungal community composition did not correlate to phenol oxidative potential overall and only more oxic soils adjacent to the river with diverse fungal communities showed declining oxidative potential after sterilization. Mn(III) addition did not significantly enhance phenol oxidative potential across all soils, although it appeared to drive fungal-mediated oxidative potential in the most aerated floodplain soils. Understanding how metals mediate SOC depolymerization as abiotic oxidants or microbially-harnessed enzyme cofactors and substrates in soils under variable hydrologic controls will improve our ability to represent depolymerization in terrestrial carbon models in wetland and other frequently saturated soils. Graphical abstract: Image 1 Highlights: Wetland soils store vast carbon stocks through oxygen limitations. We tested fungal community and redox-active metal carbon oxidation potential. Reactive Fe, but not Mn, correlated with soil carbon degradation potential. Fungal oxidative activity was only important in well-aerated, near-river soil. Drivers of floodplain soil carbon depolymerization vary within meters due to redox.